Analisa Faktor yang Mempengaruhi Kepercayaan Perdagangan Sosial dan Prilaku Pembelian dalam E-Commerce - Eryc Eryc (Teknik Informatika Universitas Pamulang, 2023)
To increase sales, e-vendors are interested in integrating social commerce features into the traditional e-commerce sites that consumers are increasingly using to make their purchasing decisions. Although the value of trust has been widely recognized in the literature, previous studies have concentrated mainly on trust in online shopping sites. It has not taken into account the multifaceted character to analyze customer behavior. This study intends to build a social commerce trust-based consumer decision making framework to gain additional insights into consumer decision making. Building social commerce trust in a multidimensional view, including trust in social media, trust in e-commerce sites, trust in social trading features, trust in customers, and buying behavior based on socio-technical theory. The data was collected from a consumer survey conducted online among social media and e-commerce users in Indonesia. The method of analyzing the collected data uses SmartPLS, namely statistics that allows the study of structural equations through modeling the path of partial least squares for testing. The aim of this research is to firmly establish the relational understanding of social trading trust and highlight its significance by examining how it influences e-commerce outcomes. This study advances theory by defining social trading beliefs and practitioners can learn more about buying behavior and applying social trading to win customers and increase sales. In addition, when developing social commerce, trust, trust in consumers, and trust in social trading features have stronger effects than trust in e-commerce websites and social media.